Escrever história, fixar o tempo: as primeiras escolhas do Instituto Histórico e Geográfico do Rio Grande do Norte (IHGRN): Writing history, setting time: the first choices of the Historical and Geographic Institute of Rio Grande do Norte (IHGRN) (Revista de História da UEG (REVHIST), 2021)
The objective of this paper is to examine the Historical and Geographic Institute of Rio Grande do Norte (IHGRN) as a social place for the production of historiographic texts, showing how they help in the process of fabricating the historical memory of the Rio Grande do Norte. The hypothesis is that this historiographic undertaking carried out by the members of the IHGRN, in the first years of its foundation, considered as one of the main strategies the establishment of a certain articulation between the time of Rio Grande do Norte and the time of the nation. Thus, to better understand this process of historiographic construction, the first articles published by the members of the IHGRN in the magazine of the association are examined, precisely, to show how this configuration reflected in the first thematic and heuristic choices, published by the magazine of the association, in initial years of its creation.Keywords: IHGRN. Historiography. Historical memory. Rio Grande do Norte.